A High Triglyceride-Glucose Index Is Associated With Contrast-Induced Acute Kidney Injury in Chinese Patients With Type 2 Diabetes Mellitus - Qin, Yuhan; Tang, Haixia; Yan, Gaoliang; Wang, Dong; Qiao, Yong; Luo, Erfei; Hou, Jiantong; Tang, Chengchun (Frontiers in Endocrinology, 2021)
Background and Objectives: Triglyceride-glucose (TyG) is an emerging vital indicator of insulin resistance and is associated with increased risk of T2DM and cardiovascular events. We aimed to explore TyG index and contrast-induced acute kidney injury (CI-AKI) in patients with type 2 diabetes underwent coronary angiology. Methods: The research enrolled 928 patients suspected coronary artery disease and underwent coronary angiology or percutaneous coronary intervention in Zhongda hospital. Patients were divided into quartiles according to the TyG index: Group 1: TyG≤8.62; Group 2: 8.62